Single-use negative pressure wound therapy reduces costs in closed surgical incisions: UK and US economic evaluation. (1st May 2021) - Nherera, Leo M; Saunders, Chris; Verma, Sanjay; Trueman, Paul; Fatoye, Francis
Abstract : Objective: Single-use negative pressure wound therapy (sNPWT) following closed surgical incisions has a demonstrable effect in reducing surgical site complications (SSC). However, there is little health economic evidence to support its widespread use. We sought to evaluate the cost-effectiveness of sNPWT compared with standard care in reducing SSCs following closed surgical incisions. Method: A decision analytic model was developed to explore the total costs and health outcomes associated with the use of the interventions in patients following vascular, colorectal, cardiothoracic, orthopaedic, C-section and breast surgery from the UK National Health Service (NHS) and US payer perspective over a 12-week time horizon. We modelled complications avoided (surgical site infection (SSI) and dehiscence) using data from a recently published meta-analysis. Cost data were sourced from published literature, NHS reference costs and Centers for Medicare and Medicaid Services. We conducted subgroup analysis of patients with diabetes, an American Society of Anesthesiologists (ASA) score ≥3 and body mass index (BMI) ≥30kg/m 2 . A sensitivity analysis was also conducted. Results: sNPWT resulted in better clinical outcomes and overall savings of £105 per patient from the UK perspective and 637 per patient from the US perspective. There were more savings when higher-risk patients with diabetes, or a BMI ≥30kg/m 2 or an ASA≥3 were considered. We conducted both one-way and probabilistic sensitivity analysis, and the results suggested that this conclusion is robust. Conclusion: Our findings suggest that the use of sNPWT following closed surgical incisions saves cost when compared with standard care because of reduced incidence of SSC. Patients at higher risk should be targeted first as they benefit more from sNPWT. This analysis is underpinned by strong and robust clinical evidence from both randomised and observational studies.